Kaleidoscopical configurations - Protasov, І.; Protasova, K. (Український математичний вісник, 2014)
Let G be a group and X be a G-space with the action G × X → X, (g, x) → gx. A subset A of X is called a kaleidoscopical configuration if there is a coloring χ : X → k (i.e. a mapping of X onto a cardinal k) such that the restriction χ|gA is a bijection for each g ∊ G. We survey some recent results on kaleidoscopical configurations in metric spaces considered as G-spaces with respect to the groups of its isometries and in groups considered as left regular G-spaces.